Comparing Mass Media in Established Democracies - Müller, L. author. aut Link
VIII, 270 p.
Keywords: This book examines the contribution of mass media to modern democracies, in comparative perspective. Part I deals with the conceptualization and implementation of a systematic framework to assess democratic media performance, both in terms of media systems and content. Part II studies media effects on the quality of democracy.